PENGEMBANGAN FORMULA KRIM NANOSQUALENE DENGAN KOMBINASI TWEEN 80 DAN PEG 400 - Septiana Indratmoko; Hanifah Nurmayadah; Andi Tenri Nurwahidah (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2019)
ABSTRACTSqualene has the benefit of being an antioxidant, maintaining moistureand softness of the skin, and has an antitumor activity. Squalene has waterinsoluble properties and is difficult to absorb in the digestive tract so thatthe level of squalene in the blood is very minimal. One form of dosagethat has a stable nature and can increase absorption of drugs isnanoparticle. This study aims to make nanosqualene cream that arephysically stable using a combination of Tween 80 and PEG 400. Thephysical properties observed include organoleptic properties,homogeneity, pH, cream type, droplet size, dispersion, adhesion andviscosity. The results showed that the nanosqualen preparation could bemade with a combination of Tween 80, PEG 400 and VCO (3,5:3,5:1) and1% squalene, droplet size of 16.3 nm. Nanosqualene cream could be madeusing high energy methods with a combination of Tween 80, PEG 400(9:1). Nanosqualene cream preparations have the following physicalproperties coconut odor, white color, semisolid form, stable,homogeneous and pH 6, O/W type, has a dispersion, adhesion andviscosity the good one.Keywords: Nanosqualen, cream, tween 80, PEG 400